2021
DOI: 10.34293/education.v9i2.3704
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Well-being of Senior Secondary School Students in Relation to Gender and Academic Achievement: An Empirical Study

Abstract: India, one of the fast growing and developing nations of the world, is doing well in growth, but it is not up to the mark in some fields. In science and technology, it is doing at par with other developed nations, and markable achievements are being touched. But in health or human growth, most of the population is not clear about the importance of health and human potentials. Many portions of the population are not aware of the positive aspects of human beings that can help them to flourish. The study has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 1 publication
0
5
0
3
Order By: Relevance
“…Students who can achieve academic goals that they set themselves are predicted to have high psychological well-being. Thus it can be said that students are able to pursue their desires, have high life satisfaction, always have a positive influence and progression (Bhat, 2021;Boudreaux & Ozer, 2013;Davis & Hadwin, 2021). High psychological well-being also occurs in students who can manage their learning activities, because several components of psychological wellbeing are growth and development, achievement of life goals, and self-regulation (Davis & Hadwin, 2021;Ryff & Singer, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Students who can achieve academic goals that they set themselves are predicted to have high psychological well-being. Thus it can be said that students are able to pursue their desires, have high life satisfaction, always have a positive influence and progression (Bhat, 2021;Boudreaux & Ozer, 2013;Davis & Hadwin, 2021). High psychological well-being also occurs in students who can manage their learning activities, because several components of psychological wellbeing are growth and development, achievement of life goals, and self-regulation (Davis & Hadwin, 2021;Ryff & Singer, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…This is because psychological well-being is related to the fulfillment of life satisfaction and individual happiness. Psychological well-being is an interesting issue because it supports individuals in achieving happiness, life satisfaction in the midst of unpleasant situations, and developing (Aydin, 2020;Bhat, 2021;Muqodas et al, 2020). The statement implies that psychological well-being is one of the important aspects that have an impact on life satisfaction and individual life happiness.…”
Section: Introductionmentioning
confidence: 99%
“…Another study during the pandemic (Wang et al, 2020a) also found that female Chinese students demonstrated a particularly high psychological impact of the outbreak by displaying higher levels of DAS, attributing it to uncertainty and potential negative impact on academic progression. On the contrary, Bhat & Jan (2023), studying the effects of gender on the mental health of Indian school students from Kashmir, found female adolescent students to have better mental health than male adolescents.…”
Section: Gender Comparisonmentioning
confidence: 99%
“…Whereas some school climates are friendly, welcoming and supporting, others are excluding, hostile and unsafe, which is why school climate may foster both favourable and unfavourable educational and psychological outcomes, becoming, in the latter case, an impediment to learning and academic performance (Kutsyuruba et al, 2015 ). In general, studies focusing on secondary education have found a significant positive association between school climate and both perceived (Daily et al, 2019 ; Escalante et al, 2021 ; Pérez et al, 2020 ) and real academic performance (Bhat & Mir, 2018 ; Demirtas‐Zorbaz et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%